2014
DOI: 10.1136/archdischild-2014-306414
|View full text |Cite
|
Sign up to set email alerts
|

The long-term outcome of patients diagnosed with sacrococcygeal teratoma in childhood. A study of a national cohort

Abstract: This is one of the largest national studies assessing the long-term outcome of patients with SCT. It highlights the significant gastrointestinal and urological long-term morbidities of SCT patients, which is useful for counselling families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 20 publications
2
16
0
1
Order By: Relevance
“…In previous studies, fecal incontinence was reported to affect 13% to 27% of the patients in all age groups, and constipation was reported to affect a wide range of 8% to 39% [5,16]. The percentage of patients in our study who developed functional sequelae is comparable to that in previous reports.…”
Section: Discussionsupporting
confidence: 86%
“…In previous studies, fecal incontinence was reported to affect 13% to 27% of the patients in all age groups, and constipation was reported to affect a wide range of 8% to 39% [5,16]. The percentage of patients in our study who developed functional sequelae is comparable to that in previous reports.…”
Section: Discussionsupporting
confidence: 86%
“…Two studies that evaluated anorectal function at adult age after SCT resection found improvement of soiling but an increasing incidence of constipation . Other studies confirmed these findings, however the majority of patients included in these studies were children …”
Section: Introductionmentioning
confidence: 90%
“…Impaired bowel function and urinary incontinence are common long‐term complications after surgery for SCT. The occurrence of such complications ranges from 19% to 38% for bowel function, and around 50% for urinary incontinence, with both occurring in 11–45.2% of cases . Risk factors include obstruction of the urinary tract and intestinal tract at prenatal imaging diagnosis, tumor recurrence, types other than Altman type I and abdominosacroperineal resection for Altman type III and IV .…”
Section: Recommendationsmentioning
confidence: 99%
“…Regarding pregnancy and delivery, 38.5% of patients were able to give birth without requiring intervention . According to a report in a Scottish national cohort, 22.2% of women >16 years of age had gone through pregnancy and given birth …”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation